Effect of the combination of remifentanil and neuromuscular blockers in pediatric endotracheal intubation: a prospective, double-blinded, randomized clinical trial - Lanxin Qiao; Di Zhang; Zhengzheng Gao; Tingting Zi; Jianmin Zhang; Lijing Li; Fang Wang (BMC Pediatrics)
Abstract Background Endotracheal intubation must be performed more carefully in children than in adults, as children are likely to more serious consequences due to the buck, move, and hemodynamic changes during the procedure. The aim of this study was to explore whether increasing the use of remifentanil during anesthesia induction can further improve the effectiveness and safety of tracheal intubation in children. Design This double-blind clinical trial included patients who underwent elective surgery under general anesthesia for intubation at Beijing Children’s Hospital. Methods One hundred thirty-eight pediatric patients aged 1–12 years, classified as having American Society of Anesthesiologists (ASA) physical status I or II, who received general anesthetics for elective surgery were randomly divided into a remifentanil group (group R) (n = 69) and a placebo group (group C) (n = 69). In group R, 1 µg/kg remifentanil was intravenously infused after the intravenous infusion of other induction drugs. In group C, the same volume of normal saline was injected intravenously. The primary outcome measure was successful intubation at the first attempt with no adverse events. Results In total, 129 patients (64 in the group R and 65 in the group C) were enrolled. The incidence of first-attempt successful tracheal intubation with no adverse events was greater in group R (87.5%, n = 56) than in group C (60.0%, n = 39) (OR, 4.7; 95% CI = 1.9–11.4; p < 0.001). Conclusions Compared with the use of cisatracurium alone, the combination of low-dose remifentanil with cisatracurium was associated with a higher rate of successful first-attempt intubation without adverse events. Trial registration Chinese Clinical Trial Registry. Retrospectively registered. Identifier: ChiCTR2400089691. Date: 13/9/2024.